Combining Life Cycle Assessment and Multi-Criteria Decision Analysis to assess agricultural waste management alternatives - Patrizia Lombardi; Elena Todella; Timothée D’Amico; Giovanni Zanderigo (Valori e Valutazioni, 2025)
Food production is a major contributor to greenhouse gas emissions and environmental damage. Urgent actions are needed to reduce climate risks, and countries are currently committed to reducing emissions in the agricultural sector. Methodologies related to Life Cycle Thinking (LCT) are widely used, focusing mainly on environmental aspects. However, a recent interest oriented toward additional aspects related to agricultural sustainability emerged, both economic and social. Within this context, this paper proposes an application of a combined evaluation framework, based on the integration of Life Cycle Assessment (LCA) with Multi-Criteria Decision Analyses (MCDAs), and, in particular, the Analytic Hierarchy Process (AHP) to assess three alternative technologies for processing orange peel waste. The present paper represents a preliminary experimental application of the proposed framework, exploring the usefulness of supporting the decision-making process in the agriculture sector through a holistic perspective and the consideration of several evaluation criteria relating to multiple – and potentially conflicting – objectives, interests, and actors, as offered by MCDAs. The evaluation of alternative valorization options is fundamental for proposing effective policies and practices, with the aim to propose a multi-dimensional perspective on agricultural waste management, including environmental, economic, and social dimensions.